Knowledge, Attitude, and Practice to COVID-19 and its Vaccines among the Lebanese Population: A Cross-sectional Study - Aalaa Saleh; Issa Awaida; Jad El Masri; Samah Al Rifai; Ahmad Al Rifai; Hossam Al Tatari (Pediatric Infectious Disease)
Aims: Assess the knowledge, attitude, and practice (KAP) toward COVID-19 and its vaccines among the Lebanese population after the beginning of the vaccination campaign and identify the different factors affecting the acceptance of vaccination. Patients and methods: The data was collected through hard copies, then it was filled in Google Form. The questionnaire included questions about sociodemographic data, dependent sources of information for COVID-19 and its vaccines, having past experience with COVID-19, and vaccination or willingness to take the vaccine at the nearest opportunity. Attitude against vaccination was assessed using a new KAP toward virus and vaccine scale consisting of 14 items. Results: The average score of the attitude of 1,002 participants was 16.87 over 28. Accepting vaccination was significantly correlated with females, having past experience with COVID-19, being a healthcare worker, participants with a higher positive attitude, and participants following official resources like governmental resources and World Health Organization (WHO) or accredited international scientific institutions rather than social media. Conclusion: The attitude toward COVID-19 and its vaccines is moderate in Lebanon, and extensive efforts are necessary for the further promotion of vaccines among the public. Social media has a high influence on the population's attitude toward vaccination, and it should be monitored strictly. Clinical significance: Social media and other factors influence on the decision on vaccination and public health.